Parâmetros térmicos da solidificação transitória sob pressão de ligas Al-10Sn-5(Cu/Si) e correlação com a microestrutura e a microdureza - Albuquerque Neto, Alfredo de Andrade (2020)
Al-Sn alloys are widely used in automotive parts, such as bearings and internal parts of combustion engines. However, the design of engines for higher loads and temperatures will require parts with greater mechanical resistance and high tribological properties. Therefore, the addition of third elements to Al-Sn alloys is an alternative for possible improvements in their properties, Copper and Silicon are identified as elements that can contribute to both the mechanical and tribological properties of the alloys. In this work, we sought to evaluate the effects of thermal solidification parameters and the addition of Cu and Si on the microstructural morphology and microhardness of Al-10% Sn alloys. To carry out the present study, a solidification experiment under pressure (100MPa) was carried out in a transient regime of heat extraction. For the Al-10Sn alloy, cell morphology was observed due to values in the order of 102 of cooling rates during the radial solidification process under pressure, where for the alloys with Cu or Si addition, dendritic morphology was obtained due to lower cooling rates compared to binary alloy, due to a constitutional supercooling (SRC) resulting from a solute rejection during solidification, where the formation of Al2Cu intermetallic for 5% Cu addition alloy and Si particles in coarse needle shapes for alloy with addition of 5% Si. The microstructural spacing of all studied alloys increased as the solidification front advanced towards the center of the ingot together with the decrease in the values of the thermal parameters (VL, TR). The microhardness of the Al-10Sn alloy remained constant (28.5HV) with the advancement of the solidification front and direction of the ingot center, however with the addition of 5% Cu or 5% Si, the Al-10Sn alloy caused an increase in the microhardness values due to the added solutes being alloy hardeners, where for the ternary alloys there was a decrease in the microhardness together with the advance of solidification towards the center of the ingot and in parallel the decrease of the values of the thermal parameters (VL, TR); The alloy with the addition of 5% Cu obtained greater microhardness when compared with the other studied alloys (Al-10Sn, Al-10Sn-5Si).